Evaluación de producción in vitro de embriones en cuyes (cavia porcellus) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Solís Campaña, Ricardo Javier (2015)
This research was developed in the installations of the Technical University of Cotopaxi by the career of Veterinary medicine in the Laboratory of reproduction biotechnology. The main aim of this work was to evaluate in vitro production of guinea pigs´ embryos, the quality of their oocytes, and the quality of embryos through the slicing technique. During the research, sixty ovaries from thirty female post-morten were collected. They were collected. They were put inside an appropriate thermos for being carried to the laboratory and so on extract the oocytes. Similarly, the male for getting out the espermatozodes. After that, they were involved into a special process to make up in vitro embryos. The in vitro embryos production was made in three important steps according to the chronological order such as oocyte maduration, fertilization of old oocyte, and embryos culture....